2017
DOI: 10.1097/pec.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intranasal Dexmedetomidine and Midazolam for Sedated Magnetic Resonance Imaging in Children

Abstract: Objective The objective of this study was to describe the use of intranasal dexmedetomidine (IN DEX) for sedated magnetic resonance imaging (MRI) examinations in children. The use of IN DEX for MRI in children has not been well described in the literature. Materials and Methods The Pediatric Sedation Research Consortium (PSRC) is a collaborative and multidisciplinary group of sedation practitioners dedicated to understanding and improving the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Dexmedetomidine is commonly used as an IV sedative agent for imaging procedures, but the IN route is gaining popularity. Sulton et al 16 demonstrated that a dose of 3 mg/kg of IN dexmedetomidine in combination with IN midazolam was effective for MRI of children. All 224 procedures were completed and There is increasing recognition that sedatives and anesthetics may cause neurotoxicity in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is commonly used as an IV sedative agent for imaging procedures, but the IN route is gaining popularity. Sulton et al 16 demonstrated that a dose of 3 mg/kg of IN dexmedetomidine in combination with IN midazolam was effective for MRI of children. All 224 procedures were completed and There is increasing recognition that sedatives and anesthetics may cause neurotoxicity in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine as a sole agent for sedation during MRI scanning of children has also been studied, with reports describing intravenous and intranasal administration. 10,15 Studies examining the use of a combination of propofol with dexmedetomidine are largely based within the OR and critical care environment; however, there are a few that look specifically at the combination in children undergoing MRI scans. There is some evidence that a bolus of 0.5 mcgkg −1 of dexmedetomidine may reduce the overall propofol requirement and decrease the need for airway support during sedation, without leading to an increase in time to discharge.…”
Section: Ta B L E 3 Comparison Of Pacu Duration By Anesthetic Techniquementioning
confidence: 99%
“…Although NICE recommends the consideration of midazolam as one of the first-line sedative drug for painless imaging procedures owing to a wide margin of safety [13], it is currently used as an adjuct sedative with either dexmedetomidine or ketamine rather than single primary agent for pediatric MRI [18,[34][35][36][37] because of the high sedation failure rates, short duration of action, as well as frequent significant respiratory depression at deeply sedating doses [38,39]. However, coadministration of midazolam and other sedative agents, especially opioids, in children is not acceptable because of siginficant increases in cardiorespiratory depression and difficulty in predicting sedation effects [9].…”
Section: ) Midazolammentioning
confidence: 99%
“…The success rate of sedation for pediatric MRI ranges from 83.3% with a 1 μg/kg bolus followed by 0.5 μg/kg/hr infusion to 98% with a 3 μg/kg bolus followed by 2 μg/kg/hr infusion [47,53]. Buccal (a mean of 2.20 ± 0.38 μg/kg) and intranasal (3 μg/kg) administration of dexmedetomidine may be useful in children with difficult IV cannulation, but their success rates of sedation for MRI are lower than IV administration and more sedative supplementation is required than IV administration [34,35,55,56]. Generally, a lack of respiratory depression combined with a relatively short half-life makes dexmedetomidine a useful single sedative agent for an ambulatory pediatric MRI setting.…”
Section: ) Dexmedetomidinementioning
confidence: 99%